а)0.5х-0.8х=9.3
-0.3х=9.3
х=9.3÷(-0.3)
х=-2.79
б)-4(х-5)+2(х-8)=-6
-4х+20+2х-16=-6
-2х+4=-6
2х=-6
х=-6÷2
х=-3
Відповідь:
Покрокове пояснення:
0,5х-0,8х=9,3
-0,3х=9,3
Перевірка
0,5*(-31)-0,8*(-31)=9,3
-15,5+24,8=9,3
б
перевірка
-4 (5-5)+2(5-8)=-6
-4*0+2*(-3)=-6
0-6=-6
а)0.5х-0.8х=9.3
-0.3х=9.3
х=9.3÷(-0.3)
х=-2.79
б)-4(х-5)+2(х-8)=-6
-4х+20+2х-16=-6
-2х+4=-6
2х=-6
х=-6÷2
х=-3
Відповідь:
Покрокове пояснення:
0,5х-0,8х=9,3
-0,3х=9,3
Перевірка
0,5*(-31)-0,8*(-31)=9,3
-15,5+24,8=9,3
б
перевірка
-4 (5-5)+2(5-8)=-6
-4*0+2*(-3)=-6
0-6=-6